Nanostructured lipid carriers and their current application in targeted drug delivery. (2nd January 2016) - Jaiswal, Piyush; Gidwani, Bina; Vyas, Amber
Abstract : In the last few decades, various drug-delivery technologies have emerged and a fascinating part of this has been the development of nanoscale drug delivery devices. Nanoparticles (NPs) and other colloidal drug-delivery systems modify the kinetics, drug distribution in the body and release profile of an associated drug. Nanostructured lipid carriers (NLCs) have been reported to be an alternative system to emulsions, liposomes, microparticles, solid lipid nanoparticles (SLNs) and their polymeric counterparts due to their numerous advantages. This paper basically reviews the types of NLCs, mechanism of skin penetration, stability related issues along with their production techniques, characterisation and applications towards targeted drug delivery.